2014
DOI: 10.1039/c3md00323j
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and functional evaluation of a mitochondria-targeted hydrogen sulfide donor, (10-oxo-10-(4-(3-thioxo-3H-1,2-dithiol-5-yl)phenoxy)decyl)triphenylphosphonium bromide (AP39)

Abstract: Mitochondrial dysfunction is observed in many diseases. Targeting H2S generation to mitochondria may be cytoprotective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 59 publications
4
104
0
Order By: Relevance
“…It has been reported that AP39 increased H 2 S generation in mitochondria, protected mitochondrial membrane potential and inhibited oxidative-stress induced cell death in cultured human endothelial cells [21, 23]. In our experiments, administration of AP39 before CPR also attenuated the increase of hydrogen peroxide levels in serum after reperfusion (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It has been reported that AP39 increased H 2 S generation in mitochondria, protected mitochondrial membrane potential and inhibited oxidative-stress induced cell death in cultured human endothelial cells [21, 23]. In our experiments, administration of AP39 before CPR also attenuated the increase of hydrogen peroxide levels in serum after reperfusion (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…To evaluate effects of AP39, we assigned mice randomly to four groups (AP39 at 10, 100 or 1000 nmol kg −1 , and vehicle) in which the study drug was administered 2 min before the initiation of CPR (Experiment 1) and three groups (AP39 at 10 or 1000 nmol kg −1 , and vehicle) in which the study drug was administered 1 min after return of spontaneous circulation (ROSC) (Experiment 2). AP39 was synthesized in-house as described [23]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that H 2 S-based therapeutic strategies may help maintain BBB integrity and decrease EDF-related stroke damage. In the same line, studies on human cerebral microvascular endothelial cells, used frequently as an in vitro model of the BBB, showed that slow-release and mitochondria-targeted H 2 S donors such as GYY4137 and AP39, respectively, prevented cellular and mitochondrial oxidative damage [72, 73]. …”
Section: H2s-related Edf In Strokementioning
confidence: 99%
“…Various H 2 S donation strategies have been developed and tested in vitro and in vivo (5,6), including renal I/R injury. The goal of the current study was to evaluate the therapeutic effect of the mitochondrially targeted H 2 S donor AP39 (7,8) in renal epithelial cells subjected to oxidative stress in vitro and in a rat model of renal ischemia in vivo . AP39 consists of a mitochondria-targeting motif, triphenyl phosphonium (TPP + ), coupled to a H 2 S-donating moiety (dithiolethione) by an aliphatic linker.…”
Section: Introductionmentioning
confidence: 99%